THEORETICAL ANALYSIS OF THE ROLE OF CHILDHOOD FEARS IN THE FORMATION OF BEHAVIORAL STEREOTYPES IN ADULTS - Vlasova, Olena; Potonska, Olha; Dembytska, Nataliia (PSYCHOLOGICAL JOURNAL, 2024)
The article is devoted to studying the important issue in psychology and psychiatry - the influence of childhood fears on adult life. It is examined from various perspectives and aspects. The research is conducted using various methods, including systemic analysis, comparative method, modeling, and classification, to gain a deeper understanding of this problem.The paper analyzes the contemporary scientific understanding of behavioral stereotypes from psychological and psychophysiological perspectives. Various determinants of the appearance of stereotypes in adult behavior and their interrelation are considered. It is crucial to identify and analyze the role of childhood fears in shaping stereotypes that determine adult behavior.After a thorough theoretical analysis and synthesis of information from professional sources, a conceptual model of the influence of childhood fears on adult behavior patterns is constructed in the paper. This model represents an important step towards further understanding and researching this complex issue.The application of the obtained results can have practical significance for psychologists, educators, teachers, and students in pedagogical, psychological, and social specialties. Understanding the influence of childhood fears on adult personality development is a key element in developing effective psychological support and intervention methods.Therefore, this article has both theoretical and practical significance and can serve as a stimulus for further research in this area.